2018
DOI: 10.1007/s11906-018-0885-8
|View full text |Cite
|
Sign up to set email alerts
|

Big Data and Blood Pressure Control: Insights from the PAMELA and BP-CARE Study Cohorts

Abstract: It is well known that only a minor fraction among the treated hypertensive patients exhibits a good blood pressure control. However, few study investigated blood pressure control on the basis not only of office, but also home and ambulatory blood pressure measurement, examining its impact on organ damage. In the whole sample of the PAMELA study, only in about 21.1% of cases treated hypertensive subjects exhibit a well-controlled office BP. Control of systolic blood pressure was rarer than the diastolic one. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
1
0
0
Order By: Relevance
“…Similarly, Mancia et al found that the frequency of masked hypertension is four times higher in people with high normal OBP [35]. These results suggest that it is related to the correlation between OBP and ABPM measurements, which have been investigated before [36]. In our study, we observed masked hypertension twice as often in patients with high normal OBP than in normotensive people.…”
Section: Discussionsupporting
confidence: 83%
“…Similarly, Mancia et al found that the frequency of masked hypertension is four times higher in people with high normal OBP [35]. These results suggest that it is related to the correlation between OBP and ABPM measurements, which have been investigated before [36]. In our study, we observed masked hypertension twice as often in patients with high normal OBP than in normotensive people.…”
Section: Discussionsupporting
confidence: 83%